Adiponectin and its Receptors as Potential Therapeutical Targets - Tilg, H.; Moschen, A. R. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2007)
The adipose tissue-derived protein adiponectin is involved in the regulation of insulin sensitivity, inflammation and immunity. Circulating levels of this adipocytokine are decreased in obesity and diseases associated with insulin resistance. Besides its major role in regulation of hepatic insulin sensitivity, recent evidence suggests a strong antiinflammatory function for this pleiotropic mediator. Whereas initial studies demonstrated that adiponectin suppresses primarily the pro-inflammatory cytokine tumor necrosis factor-alpha, current studies show that it induces anti-inflammatory cytokines such as interleukin-10 or IL-1 receptor antagonist. These effects are paralleled by other immune-regulatory properties such as downregulation of endothelial cell adhesion molecules. This adipocytokine suppresses inflammation in various models of liver and myocardial injury. Adiponectin exerts its biological functions by interacting with adiponectin receptor type 1 and 2 as well as T-cadherin. Adiponectin is a key mediator regulating and affecting processes between adipose tissue, inflammation and immunity. Therefore, adiponectin, adiponectin secretion-stimulating agents or adiponectin receptor agonists might be of clinical relevance in many diseases beyond those associated with insulin resistance. Better knowledge of the complex biology of adiponectin and its receptors may indeed provide novel therapeutic approaches.
Keywords: adiponectin receptor type 1 and 2